George W. Bush, the American Press, and the Initial Framing of the War on Terror after 9/11 - Althouse, Matthew T. (2012)
President George W. Bush's speech to the General Assembly of the United Nations on November I 0, 200 I, marks an important moment in the history of the War on Terror. 1 It followed closely upon the joint U.S.-Northern Alliance military capture of Mazari Sarif, Afghanistan, which significantly disrupted the Taliban's operations and arguably marked the official beginning of America's War on Terror. As President Bush stated, The time for sympathy has now passed; the time for action has now arrived. 2 In some ways, the speech offered nothing new. It reiterated words and ideas that the president frequently used to label elements of the situation following the 9/11 attacks